1995
DOI: 10.1254/jjp.67.233
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dilazep: II. Dilazep Attenuates Lysophosphatidylcholine-Induced Mechanical and Metabolic Derangements in the Isolated, Working Rat Heart

Abstract: ABSTRACT-The effects of dilazep, d-propranolol and lidocaine on the mechanical and metabolic changes induced by lysophosphatidylcholine (LPC) were studied in isolated, perfused working rat heart. After a stabilization period, the heart was perfused for 5 min with LPC (10 €M) alone, LPC plus dilazep (5, 10 or 20 pM), LPC plus d-propranolol (30 or 50 pM) or LPC plus lidocaine (30 or 100 pM) and then perfused with normal Krebs-Henseleit bicarbonate (KHB) buffer for a further 20 min. Perfusion with LPC for 5 min f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The cardiac ac tion of lysophosphatidylcholine is similar to or identical with that of palmitoyl-L-carnitine; it produces intracellu lar Ca 2+ accumulation through long-lasting bursts of Na+ channel openings (24). Recently, Hoque et al (25) have demonstrated that dilazep attenuates the mechanical dysfunction and metabolic derangements induced by lysophosphatidylcholine in the isolated working rat heart. Kang and Leaf (26) have shown that tetrodotoxin attenu ates the lysophosphatidylcholine-induced arrhythmias in rat myocytes.…”
Section: Discussionmentioning
confidence: 97%
“…The cardiac ac tion of lysophosphatidylcholine is similar to or identical with that of palmitoyl-L-carnitine; it produces intracellu lar Ca 2+ accumulation through long-lasting bursts of Na+ channel openings (24). Recently, Hoque et al (25) have demonstrated that dilazep attenuates the mechanical dysfunction and metabolic derangements induced by lysophosphatidylcholine in the isolated working rat heart. Kang and Leaf (26) have shown that tetrodotoxin attenu ates the lysophosphatidylcholine-induced arrhythmias in rat myocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover it has been found that the increase in [Ca2+]i induced by LPC can be inhibited by flunarizine (Ver Donck et al, 1992), which possesses high lipophilicity (Michiels et al, 1983). Our previous study (Hoque et al, 1995) revealed that non-esterified fatty acids (NEFA) accumulate in the myocardium after addition of exogenous LPC in perfused rat hearts, and (+ )-propranolol inhibited the accumulation of NEFA. This result indicates that LPC accelerates catabolism of membrane phospholipids, and (+)-propranolol inhibits it.…”
Section: Effects Of Lpc On [Ca2 ]I and Cell-shapementioning
confidence: 99%
“…Because of both hydrophilic and hydrophobic properties, LPC can easily exert deleterious effects on biological membrane systems and cause electrophysiological alterations and mechanical dysfunction (Corr et al, 1984;Das et al, 1986;Datorre et al, 1991;Hoque et al, 1995). Therefore, LPC has been suspected as one of the mediators of ischaemic injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABSTRACT-Global ischemia (15 min) followed by reperfusion (10,20 Dilazep has been demonstrated to attenuate myocardial ischemic damage (1,2). The cardioprotective action of dilazep has been considered to be due to potentiation of the cardiovascular effects of adenosine, such as vasodilat ing and negative chronotropic effects, through inhibition of adenosine uptake into cardiac and endothelial cells (3).…”
mentioning
confidence: 99%